Pengaruh Keselamatan dan Kesehatan Kerja (K3) dan Lingkungan Kerja terhadap Kinerja Karyawan - Alamsyah, Mochamad Zidan; Endayani, Fatmasari; Sulistyorini, Ery; Puspasari, Ernita Dian; Yulistiowati, Irma Mufita (Business Management Research, 2024)
This research aims to determine the impact of health and safety at work and the work environment on employee performance. The population in this study consists of 75 employees of UD. Zidan Putra. This research is an explanatory study and utilizes a quantitative approach. The data analysis techniques used in this study are descriptive analysis and regression analysis. The sampling technique used in this research is a saturated sampling technique. The results of the research found that health and safety at work and the work environment significantly impact employee performance. It is revealed that the work environment has a more significant impact on employee performance in this case.